2022
DOI: 10.1002/art.41963
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Rheumatoid Arthritis Through the Inhibition of Tumor Necrosis Factor–Induced Caspase 3/Gasdermin E–Mediated Pyroptosis

Abstract: To determine the role of gasdermin E (GSDME)-mediated pyroptosis in the pathogenesis and progression of rheumatoid arthritis (RA), and to explore the potential of GSDME as a therapeutic target in RA.Methods. The expression and activation of caspase 3 and GSDME in the synovium, macrophages, and monocytes of RA patients were determined by immunohistochemistry, immunofluorescence, and Western blot analysis. The correlation of activated GSDME with RA disease activity was evaluated. The pyroptotic ability of monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…A recent study also showed that GSDMD-mediated monocytes pyroptosis was involved in persistent inflammatory cytokine release in RA pathology ( Wu et al, 2020 ). The latest research ultimately studied the pathogenic role of GSDME in monocytes, macrophages and animal models of RA, suggesting that GSDME might be a potential therapeutic target for RA ( Zhai et al, 2021 ). However, involvement of GSDME-mediated pyroptosis in the function of RA-FLSs has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also showed that GSDMD-mediated monocytes pyroptosis was involved in persistent inflammatory cytokine release in RA pathology ( Wu et al, 2020 ). The latest research ultimately studied the pathogenic role of GSDME in monocytes, macrophages and animal models of RA, suggesting that GSDME might be a potential therapeutic target for RA ( Zhai et al, 2021 ). However, involvement of GSDME-mediated pyroptosis in the function of RA-FLSs has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this feature, pyroptosis might play a crucial role in the genesis and development of RA. A study has implicated the importance of GSDMD-mediated monocytes pyroptosis in RA pathology ( Wu et al, 2020 ), and Ze-Qing Zhai’s latest article revealed a pathogenic role of GSDME in the pyroptosis of monocytes and macrophages in RA ( Zhai et al, 2021 ). However, the occurrence of pyroptosis as well as its mechanism and effect in RA-FLSs remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the increased trimethylamine-N-oxide in periodontitis patients damages peripheral endothelial progenitor cells through pyroptosis driven by Bax/caspase-3/GSDME pathway, suggesting that GSDME activation may also be associated with endothelial dysfunction in periodontitis patients ( Zhou et al, 2021 ). More recently, studies have certified that pyroptosis mediated by the caspase-3/GSDME axis is also concerned with inflammatory skin diseases ( Liu J. et al, 2021 ), idiopathic inflammatory myopathies ( Liu M. et al, 2020 ) and rheumatoid arthritis ( Zhai et al, 2022 ). These researches demonstrated that GSDME has been identified as a potential therapeutic target for inflammation.…”
Section: The Role Of Gsdme In Diseasesmentioning
confidence: 99%
“…On the other hand, GSDME-induced pyroptosis and the consequent inflammatory response contributes to H7N9 influenza-mediated lethality in mice [ 124 ]. Recent findings also correlate GSDME levels and activation in patient intestinal mucosa or synovial immune cells with Crohn's disease and rheumatoid arthritis severity, respectively, and mice deficient in GSDME were protected from chemical-induced (2,4,6-trinitrobenzenesulfonic acid) colitis or collagen-induced arthritis [ 125 , 126 ]. These studies highlight how an excess of GSDME-driven cell death can cause pathological inflammatory responses.…”
Section: Apoptotic Activation Of Pyroptosis By Caspase-3 Cleavage Of ...mentioning
confidence: 99%